The capitalistic function of education-directed social responsibility projects in Turkey within the context of relationships between the private sector and NGOs - Bicakci, Ilker C. (INST EDUCATION POLICY STUDIES, 2008)
Similar to other underdeveloped countries, the Republic of Turkey is also faced with high levels of poverty and unemployment, and to ameliorate these problems the state has traditionally devoted much of its social welfare efforts towards improving health and education. Certain private sector corporations also recognize that to grow and advance their own organizations it is imperative that they too contribute to these welfare efforts. They are also cognizant of the fact that they have to preserve their prestige and win the sympathy of the society if they hope to preserve their economic lives. To this end many of these corporations are conducting social responsibility projects, generally doing so in collaboration with various non-governmental organizations (NGO's). The projects directed towards developing educational opportunities not only contribute-even if in a limited fashion
Keywords: Social Responsibility; Educational Policy; Private Sector; NGOs; Education & Educational Research